Human Trafficking in Costa Rica: Legal Elements for Understanding - Mora-Barquero, Alonso (2023)
In Costa Rica, there are no studies on the legal and criminal interpretation regarding the crime of human trafficking, creating a knowledge gap. This study aims to fill that void. The main objective is to analyze the concept of human trafficking as outlined in the Palermo Protocol and how it is incorporated and understood within Costa Rican legislation. This analysis provides clarity for research, prevention, prosecution, and punishment of the crime, as well as enhanced access to justice, care, and protection for the victims. The study takes a descriptive legal approach, with a focus on International Law, collecting and examining judicial resolutions and elements from both national and international legislation, drawing upon the hierarchical character of the international instruments ratified by Costa Rica. The main finding is that while Costa Rica has limited jurisprudence on the crime of human trafficking, it has established fundamental elements for understanding this phenomenon. For instance, human trafficking is considered a multi-offensive crime that affects personal legal assets, primarily human dignity, and it is a crime with anticipated consummation.